Anatomical-Based Diagnosis and Filler Injection Techniques: Lips and Philtrum - Hong, Gi-Woong; Choi, Wonseok; Yoon, Song-Eun; Wan, Jovian; Yi, Kyu-Ho (Life (Basel, Switzerland), 2025)
Lip augmentation has become increasingly popular in aesthetic medicine, driven by advancements in dermal filler technologies and injection techniques. This review provides a comprehensive overview of lip anatomy, age-related changes, and current best practices in lip augmentation using dermal fillers. The complex structure of the lips, including multiple layers of skin, muscle, and mucosa, contributes to their unique appearance and function. Age-related changes, such as volume loss, thinning of the vermilion border, and flattening of the philtrum, significantly impact lip aesthetics. Understanding these changes is crucial for developing effective treatment strategies. The review discusses the importance of tailoring treatments to individual patient needs, considering factors such as ethnic variations in lip structure and cultural preferences. It emphasizes the significance of proper filler selection, with hyaluronic acid-based products being the gold standard due to their biocompatibility and reversibility. Injection techniques, including needle and cannula approaches, are described in detail, with a focus on safety and optimal aesthetic outcomes. Anatomical considerations, particularly the vascular supply to the lips, are highlighted as critical for avoiding complications during filler injections. The review also addresses the evolving approach to lip augmentation, which now focuses on restoring natural contours and addressing age-related changes in the perioral region rather than simply increasing volume. Finally, the importance of managing patient expectations and the potential for future advancements in the field are discussed, including the development of more targeted filler products and refined injection techniques.